PENINGKATAN HASIL BELAJAR MATA PELAJARAN PEKERJAAN DASAR OTOMOTIF (PDO) KELAS X DENGAN METODE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) di SMK N 3 YOGYAKARTA - Sujiyanto Sujiyanto (Jurnal Pendidikan Vokasi Otomotif, 2019)
This study aimed to improve students’ participation and learning achievement using Students Team Achievement Division (STAD) on the Basic Automotive course. This classroom action research was performed consisting of three cycles. Each cycle consisted of planning, action, observation, and reflection.  There were 31 students from SMK Negeri 3 Yogyakarta selected as participants for the study. Data were collected using observation sheet and test at the beginning and end of classroom activities. The results of this study indicated that implementing STAD method can improve students’ learning outcomes. There were seventy percent or more (≥ 70%) students actively participated in the classroom activities. Furthermore, there were eighty percent or more (≥ 80%) students reached higher score than the minimum requirement for their test.